2012
DOI: 10.1002/mabi.201200317
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Fibrous Networks of Cellulose Nanofibres and Collagen Crosslinked Using Genipin: Potential as Artificial Ligament/Tendons

Abstract: Bio-based fibrous nanocomposites of cellulose nanofibres and non-crosslinked/crosslinked collagen were prepared by in situ pH-induced fibrillation of collagen phase and sterilized using gamma rays at 25 KGy. Collagen phase is crosslinked using genipin, a bio-based crosslinker that introduces flexible crosslinks. Microscopy studies of the prepared materials showed nanostructured fibrous collagen and cellulose dispersed in collagen matrix. Mechanical performance of the sterilized nanocomposites was close to that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
38
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 20 publications
3
38
0
1
Order By: Relevance
“…CNFs have been investigated as a promising substrate for regenerative medicine and wound healing such as scaffolds for tissue-engineered meniscus, blood vessels, and ligament or tendon substitutes (Mathew et al 2011(Mathew et al , 2012Jia et al 2013;Mathew et al 2013;Lin and Dufresne 2014). The applicability of CNFs as hemodialysis membranes (Ferraz et al 2012(Ferraz et al , 2013, antimicrobial nanomaterials (Martins et al 2012;Liu et al 2014) and in the pharmaceutical industry as films for long-lasting sustained drug delivery (Valo et al 2011;Kolakovic et al 2012) has also been documented.…”
Section: Introductionmentioning
confidence: 98%
“…CNFs have been investigated as a promising substrate for regenerative medicine and wound healing such as scaffolds for tissue-engineered meniscus, blood vessels, and ligament or tendon substitutes (Mathew et al 2011(Mathew et al , 2012Jia et al 2013;Mathew et al 2013;Lin and Dufresne 2014). The applicability of CNFs as hemodialysis membranes (Ferraz et al 2012(Ferraz et al , 2013, antimicrobial nanomaterials (Martins et al 2012;Liu et al 2014) and in the pharmaceutical industry as films for long-lasting sustained drug delivery (Valo et al 2011;Kolakovic et al 2012) has also been documented.…”
Section: Introductionmentioning
confidence: 98%
“…They form hydrogels with tuneable physical and chemical properties [24,25] and are shown to be non-cytotoxic [26]. Therefore, they have diverse pharmaceutical and biomedical applications [27][28][29]. When used in cell culture, the NFC hydrogel is mixed with cells without any polymerization process.…”
mentioning
confidence: 99%
“…8,9,14,15 Our earlier studies have also demonstrated that solution cast brous nanocomposite structures with high cellulose nanobers concentrations (75 wt%) and collagen provide mechanical performance suitable for ligaments. 8,9 Also, our previous studies have demonstrated the noncytotoxicity of nanocellulose from different sources and their potential in medical applications.…”
mentioning
confidence: 99%
“…8,9,14,15 Our earlier studies have also demonstrated that solution cast brous nanocomposite structures with high cellulose nanobers concentrations (75 wt%) and collagen provide mechanical performance suitable for ligaments. 8,9 Also, our previous studies have demonstrated the noncytotoxicity of nanocellulose from different sources and their potential in medical applications. 15,19,20 In the current study, 3D nanocomposite scaffolds for cartilage regeneration were processed via freeze-drying technique, where porous cellulose nanober structures were bound together and mechanically/dimensionally stabilized using low amounts of crosslinked chitosan/gelatin blend system.…”
mentioning
confidence: 99%
See 1 more Smart Citation